Pengaruh Kecepatan Putar Dan Kapasitor Pararel Pada Belitan Bantu Terhadap Keluaran Generator Induksi 1 Fase 6 Kutub - Triatmanto, Anhar, Agus Supardi, S.T., M.T (2016)
Renewable energy power plants is still very little used in Indonesia. The use of renewable electricity generation by using highly precise induction generator to be used because it has the reliability, high efficiency, easy maintenance and uncomplicated operation. Induction generator also has a simple shape so it can be placed at a location such as hydro and wind power plant. This study will examine the influence of rotational speed and capacitors to the output of induction generator in no-load and loaded with energy sving lamps. At the time of the test capacitor connected in parallel to the auxiliary winding while the load and measuring devices connected to the main winding of induction generator. Induction generator used has a capacity of 1 HP with 6 pole stator design. The test results showed capacitors used for excitation of 72 μF connected in parallel to the auxiliary winding to generate a voltage. Operation of the generator with the generator coupple of primemover. The induction generator in no-load condition capable generate a voltage of 220 volts at initial speed 1200 rpm and voltage of 185.2 volts at initial speed 1100 rpm. When loaded, the voltage and frequency drop occurred during burdened with the highest power (120 watts) at the initial speed 1200 rpm resulting in a voltage of 196 volts and a frequency of 57.8 Hz whereas the initial speed of 1100 rpm generated a voltage of 156.2 volt and a frequency of 51.5 Hz. Voltage and frequency variations are influenced by an increase in load power. The increase in power load resulted in higher voltage and frequency is decreased.